Determinants of Fraudulent Financial Statements Using an Approach Fraud Hexagon - Azhari, Hana; Lenggogeni, Lenggogeni (Dinasti International Journal of Economics, Finance & Accounting, 2024)
There are 239 cases of fraud in Indonesia with a percentage of cases of financial statement fraud of 9.2%, so this research aims to develop methods for preventing and detecting financial statement fraud are needed. The theory used is the latest theory, namely the fraud hexagon. This research is quantitative. This research is a hypothesis testing research which aims to test hypotheses and explain phenomena in the form of relationships between variables in the research, namely the fraudulent financial statement variable as the dependent variable and the elements in the fraud hexagon, namely pressure, opportunity, rationalization, capability, arrogance and collusion as independent variables. The novelty of this research is this research added a moderating variable which is exposures. The primary data used was taken directly using a questionnaire distributed to practitioners in the finance, accounting and internal audit departments in the state-owned enterprises in services industry from Nov 3rd 2023 until Dec 2nd 2023 with 139 respondents used. This research has 7 hypotheseses with 6 of them are every elements in fraud hexagon has positive effect to fraudulent financial statements, and the 7th hypotheses is exposures moderates in weaken the influence of the variables in fraud hexagon to fraudulent financial statement. The results of this research is pressure, capability, collusion, opportunity, and arrogance has positive significant effect in fraudulent financial statement, as for rationalization has no significant effect in fraudulent financial statement. Exposures can moderate elements in fraud hexagon in weaken their influence in fraudulent financial statement.